2018
DOI: 10.1002/pbc.27067
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and clinical characteristics of nontransfusion‐dependent thalassemia in the United States

Abstract: NTDT in the United States is a multi-ethnic disease with different genotypic mutations and phenotypic manifestations. A higher than expected proportion of patients was Black/African American. NTDT-related complications are common and increase with age, supporting a need for early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…β‐TI is a transfusion‐independent form of thalassemia. Most transfusion‐independent thalassemia patients are of Caucasian or African descent . Patients with β‐TI usually present with milder clinical symptoms and a later onset of hemolytic anemia compared with those with β‐TM.…”
Section: Discussionmentioning
confidence: 99%
“…β‐TI is a transfusion‐independent form of thalassemia. Most transfusion‐independent thalassemia patients are of Caucasian or African descent . Patients with β‐TI usually present with milder clinical symptoms and a later onset of hemolytic anemia compared with those with β‐TM.…”
Section: Discussionmentioning
confidence: 99%
“…More recent estimates from Europe suggest there are approximately 7000 patients in Italy (0.012% of a total population of approximately 60 million) and 3241 patients in Greece (0.029% of a total population of 11 million) with thalassemias . Modern patterns of increased migration have resulted in thalassemias becoming widespread in other regions, as illustrated by a report from the Centers for Disease Control that reported that 27% of people with nontransfusion‐dependent β‐thalassemia (NTDT) in North America were born overseas …”
Section: Introductionmentioning
confidence: 99%
“…Seminal articles on studies he led or contributed mightily to include demonstrating that newborn screening for SCD prevented deaths, phenotypic matching for red blood cell antigens as necessary to prevent alloimmunization, preoperative transfusion in SCD, and causes and outcomes of acute chest syndrome . Many other important studies and observations have contributed to our knowledge of the natural history and pathophysiology of hemoglobinopathies, interventions, and management of complications . He recently published a large multicenter randomized controlled trial demonstrating the benefit of L‐glutamine in decreasing the rate of acute vaso‐occlusive pain in SCD.…”
mentioning
confidence: 99%
“…4 Many other important studies and observations have contributed to our knowledge of the natural history and pathophysiology of hemoglobinopathies, interventions, and management of complications. [5][6][7][8][9][10][11][12][13][14][15] He recently published a large multicenter randomized controlled trial demonstrating the benefit of L-glutamine in decreasing the rate of acute vaso-occlusive pain in SCD. L-glutamine is only the second Food and Drug Administration-approved therapy for SCD.…”
mentioning
confidence: 99%